A a new digital value chain model with PLC in biopharmaceutical industry: The implication for open innovation - YongChan Kim; Erdal Atukeren; YeonWoo Lee (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The advancement of technology in the biopharmaceutical industry has spearheaded the speed and scale of digitalization in various aspects. New drug development is becoming more complex, costly, and challenging. This paper examines how the pharmaceutical value chain model could integrate with the product-life-cycle perspective to better explain the drug development process changes and how the digital transformation could be implemented at each stage of the drug development process. We suggest a new framework to capture digital value creation in the biopharmaceutical industry by focusing on the specific processes in new drug development and integrating the product life cycle management and value chain model. The new framework has operational implications for the biopharmaceutical industry, where digital transformation can simplify and increase the efficiency in each phase, from drug discovery, clinical trials, regulatory, manufacturing, commercialization, to monitoring processes.
Keywords: 650; pharmaceutical industry; value chain; product life cycle management; drug developmentprocess; digital transformation; technology adoption; industry transformation; research anddevelopment; open innovation; innovation policy